Regulatory roles of external cholesterol in human airway epithelial mitochondrial function through STARD3 signalling. Issue 6 (9th June 2022) - Li, Liyang; Liu, Yifei; Liu, Xuanqi; Zheng, Nannan; Gu, Yutong; Song, Yuanlin; Wang, Xiangdong
Abstract: Background: Hypercholesterolemia is found in patients with chronic lung inflammation, during which airway epithelial cells play important roles in maintenance of inflammatory responses to pathogens. The present study aims at molecular mechanisms by which cholesterol changes airway epithelial sensitivity in response to smoking. Methods: Human bronchial epithelial cells (HBEs) were stimulated with cigarette smoke extract (CSE) and mice were exposed to CS/lipopolysaccharide (LPS) as models in vitro and in vivo. Severe COPD patients and healthy volunteers were also enrolled and the level of cholesterol in plasma was detected by metabolomics. Filipin III and elisa kits were used to stain free cholesterol. Mitochondrial function was detected by mitotracker green, mitotracker green, and Seahorse. Mitochondrial morphology was detected by high content screening and electron microscopy. The mRNA and protein levels of mitochondrial dynamics‐related proteins were detected by RT‐qPCR and Western blot, respectively. BODIPY 493/503 was used to stain lipid droplets. Lipidomics was used to detect intracellular lipid components. The mRNA level of interleukin (IL)‐6 and IL‐8 were detected by RT‐qPCR. Results: We found that the cholesterol overload was associated with chronic obstructive pulmonary disease (COPD) and airway epithelia‐driven inflammation, evidenced by hypercholesterolemia in patients with COPD and preclinical models, alteration of lipid metabolism‐associated genes in CSE‐induced airway epithelia and production of ILs. External cholesterol altered airway epithelial sensitivity of inflammation in response to CSE, through the regulation of STARD3‐MFN2 pathway, cholesterol re‐distribution, altered transport and accumulation of cholesterol, activities of lipid transport regulators and disorder of mitochondrial function and dynamics. MFN2 down‐regulation increased airway epithelial sensitivity and production of ILs after smoking, at least partially by injuring fatty acid oxidation and activating mTOR phosphorylation. Conclusions: Our data provide new insights for understanding molecular mechanisms of cholesterol‐altered airway epithelial inflammation and for developing diagnostic biomarkers and therapeutic targets to improve patient outcomes. Abstract : STARD3, upregulated in COPD, could help cholesterol transfer to mitochondria and lead to mitochondrial dysfunction. Exogenous cholesterol reversed the protective MFN2 upregulation in CSE stimulation and exacerbated the mitochondrial dysfunction. Mitochondrial dysfunction caused by MFN2 downregulation altered the lipid homeostasis related to the activation of mTOR.